Identification of four secretory phospholipase A2s in a lepidopteran insect, Acrolepiopsis sapporensis, and their functional association with cellular immune responses - Hrithik, Md Tafim Hossain; Hong, Jooan; Kim, Yonggyun (Frontiers in Endocrinology, 2023)
Background: Eicosanoids are a group of the oxygenated C20 polyunsaturated fatty acids and play crucial roles in mediating various insect physiological processes. Catalytic activity of phospholipase A2 (PLA2) provides an initial substrate, arachidonic acid (AA), for subsequent eicosanoid biosynthesis. Results: This study identified four different secretory PLA2 (As-PLA2A  As-PLA2D) genes encoded in the Asian onion moth, Acrolepiopsis sapporensis. A phylogenetic analysis indicated that As-PLA2A and As-PLA2D are clustered with Group III PLA2s while As-PLA2B and As-PLA2C are clustered with Group XII and Group X PLA2s, respectively. Expression levels of these PLA2 genes increased along with larval development especially in the fat body. A bacterial immune challenge up-regulated the basal expression levels of the four PLA2 genes which resulted in significant increases of the PLA2 enzyme activity. The enzyme activity was susceptible to calcium chelator or reducing agent, suggesting Ca2+ dependency and disulfide linkage required for the catalytic activities of the secretory type of PLA2s. In addition, the PLA2 activity was also susceptible to bromophenol bromide (BPB), a specific inhibitor to sPLA2, but not to intracellular PLA2 inhibitors. An addition of BPB to the immune challenge significantly prevented hemocyte-spreading behavior of A. sapporensis. BPB treatment also suppressed a cellular immune response measured by hemocyte nodule formation. However, the immunosuppression was significantly rescued by the AA addition. To determine the PLA2(s) responsible for the immunity, individual RNA interference (RNAi) treatments specific to each of the four PLA2s were performed. Injection of gene-specific double-stranded RNAs caused significant reductions in transcript level in all four PLA2s. In all four PLA2s, the RNAi treatments prevented the cellular immune response even after the immune challenge. Conclusions: This study reports four secretory PLA2s encoded in A. sapporensis and their function in mediating cellular immunity.